Stakeholders-Driven Process Mining Method for Analyzing Emergency Department Processes - Al-Dowail, Mohammed; Al-Hashedi, Abdullah (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The emergency department is the most critical in the hospital. It has a high level of complexity because of the admission of patients with a wide range of diseases and various urgent cases, resulting in a variety of issues such as overcrowding, extended waiting periods, and inefficient resources utilization. Process mining is a new business intelligence framework that focuses on analyzing processes by extracting knowledge from the event log. This paper aims to introduce a method for analyzing emergency department processes using process mining techniques. It is an extension and based on previous methods, with additional phases that suit the complexity of the emergency environment, as well as involve the stakeholder in most phases. It will help you understand the varied patient pathways taken by different groups of patients as well as offer insight into bottlenecks. As a result, the procedures become more efficient.